Stability of MDS-UPDRS Motor Subtypes Over Three Years in Early Parkinson's Disease - Kohat, Abhijeet K.; Ng, Samuel Y. E.; Wong, Aidan S. Y.; Chia, Nicole S. Y.; Choi, Xinyi; Heng, Dede L.; Li, Wei; Ng, Hwee-Lan; Chua, Shu-Ting; Neo, Shermyn X. M.; Xu, Zheyu; Tay, Kay-Yaw; et al. (Frontiers in Neurology, 2021)
Background: Various classifications have been proposed to subtype Parkinson’s disease (PD) based on their motor phenotypes. However, the stability of these subtypes has not been properly evaluated. Objective: The goal of this study was to understand the distribution of PD motor subtypes, their stability over time, and baseline factors that predicted subtype stability. Methods: Participants (n=170) from two prospective cohorts were included: The Early PD Longitudinal Singapore (PALS) study and National Neuroscience Institute Movement Disorders Database. Early PD patients were classified into Tremor dominant (TD), postural instability and gait difficulty (PIGD), and Indeterminate subtypes according to the Movement Disorder Society’s Unified PD Rating Scale (MDS-UPDRS) criteria, and clinically evaluated for 3 consecutive years. Results: At baseline, 60.6% patients were TD, 12.4% patients were Indeterminate, and 27.1% patients were PIGD subtypes (p < 0.05). After three years, only 62% of patients in TD, and 50% of patients in PIGD subtypes remained stable. The mean Levodopa equivalent daily dose (LEDD) was higher in PIGD subtype (276.92±232.91 mg; p=0.01). Lower LEDD (p<0.05, OR 0.99, 95%CI:0.98-0.99) and higher TD/PIGD ratios (p<0.05, OR 1.77, 95%CI:1.29-2.43) were independent predictors of stability of TD subtype with an AUC of 0.787 (95%CI:0.669 - 0.876), sensitivity = 57.8% and specificity = 89.7%. Conclusion: Only 50-62% of PD motor subtypes as defined by MDS-UPDRS remained stable over 3 years. TD/PIGD ratio and baseline LEDD were independent predictors for TD subtype stability over 3 years. Keywords: Parkinson’s disease, Tremor, Levodopa, Disease progression